Motor Learning Improves the Stability of Large-Scale Brain Connectivity Pattern - Yu, Mengxia; Song, Haoming; Huang, Jialin; Song, Yiying; Liu, Jia (Frontiers in Human Neuroscience, 2020)
Repeated practice is fundamental to acquisition of skills, which is typically accompanied by increasing reliability of neural representations that manifested as more stable activation patterns for the trained stimuli. However, large-scale neural pattern induced by learning has been rarely studied. Here we investigated whether global connectivity pattern became more reliable as a result of motor learning using a novel analysis on multivariate pattern of functional connectivity (MVPC). Human participants were trained with a finger-tapping motor task for five consecutive days and went through functional magnetic resonance imaging scanning before and after training. We found that motor learning increased the whole-brain MVPC stability of the primary motor cortex (M1) when participants performed the trained sequence, while no similar effects were observed for the untrained sequence. Moreover, the increase of MVPC stability correlated with participants’ improvement in behavioral performance. These findings suggested that acquisition of motor skills was supported by the increased connectivity pattern stability between the M1 and the rest of the brain. In summary, our study not only suggests global neural pattern stabilization as a neural signature for effective learning, but also advocates applying the MVPC analysis to reveal mechanisms of distributed network reorganization supporting various types of learning.